Digital Portfolios in English Language Teaching: A Systematic Review of Trends, Benefits, and Future Directions - Titis Dewi Cakrawati; Rolisda Yosintha (Metathesis: Journal of English Language, Literature, and Teaching, 2025)
The current study examines the trends and main results of the research on the e-portfolios use in English language teaching within the last ten years. For this aim, the researchers reviewed various databases, including Google Scholar, Eric, Taylor & Francis, and Scopus, and investigated 17 journal articles that meet the criteria. The research used a systematic review as the research methodology, with content analysis to analyze the data. The findings showed that e-portfolios have been widely employed to teach English for more than ten years, with the number of research in the area rapidly increasing in the last two years (2022-2023). Furthermore, the most used research methods were experimental studies, with some claims that they can successfully improve the learners’ English skills. Besides, writing and vocabulary were the common language skills to learn. A further analysis revealed opportunities for the use of e-portfolios in English classrooms. Additionally, in the reviewed studies on the effectiveness of e-portfolios in English language teaching, the findings suggested the advantages of e-portfolios. Based on the reviews, some recommendations and suggestions were made for teaching practitioners and future research.